Soldiers and Trauma - Wolfgang Stojetz (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Understanding the risks and consequences of military service in fragile regions is a vital concern facing veterans and policymakers in Germany (and many other nations). Researchers, health professionals, politicians and the news media are actively discussing this contentious topic. A key point in the debate is the psychological well-being of discharged servicemen. The purpose of this column is to offer a perspective on prevalent opinions and evidence regarding the question: What are the risks of deployment in a fragile region for the psychological health of military personnel?
Keywords: 330